Review of the genus classification of Abiinae (Cimbicidae, Hymenoptera) - Vilhelmsen, Lars; Shinohara, Akihiko (European Journal of Taxonomy, 2020)
Abiinae is the second-largest subfamily in Cimbicidae, a small family of true sawflies (Tenthredinoidea). The subfamily is adequately defined, but the generic classification has been unstable. Currently, only two genera are regarded as valid: Abia Leach, 1817 and Allabia Semenov & Gussakovskij, 1937. We evaluate the generic classification of Abiinae in a phylogenetic context. A total of 32 species (out of 57 described for the subfamily), including the type species of Allabia, Allabia infernalis (Semenov, 1896), are scored for 150 adult morphological characters. Results show some resolution, but only few clades can be circumscribed by consistent character combinations. Most of the characters that have previously been used to define genera are not congruent; consequently, most suggested genus definitions appear to be random character state combinations and few natural groups can be identified. For these reasons, we treat Allabia syn. nov. as a junior synonym of Abia and make the following additional taxonomic changes: Abia infernalis Semenov, 1896 comb. rev. and Abia malaisei (Semenov & Gussakovskij, 1937) syn. nov. For the purpose of long-term stability of the classification of Abiinae, we recommend recognizing only one genus, Abia, within the subfamily.